Comparison of Escherichia coli and Klebsiella pneumoniae Acute Pyelonephritis in Korean Patients - Hyun, Miri (Infect Chemother, 2019)
BACKGROUND: Escherichia coli and Klebsiella pneumoniae are two of the most common causes of urinary tract infection. The purpose of this study was to compare clinical characteristics and antimicrobial susceptibility of acute pyelonephritis (APN) between E. coli and K. pneumoniae. MATERIALS AND METHODS: We retrospectively reviewed medical records of patients with APN due to E. coli and K. pneumoniae between February 2014 and October 2017. RESULTS: A total 329 patients were enrolled; 258 cases of E. coli and 71 cases of K. pneumoniae. Among them, 219 cases were categorized into community-onset APN; 194 cases of E. coli and 25 cases of K. pneumoniae, and 110 patients were categorized into healthcare-associated APN; 64 cases of E. coli and 46 cases of K. pneumoniae. Catheter-associated APN was more frequently observed in K. pneumoniae in both community-onset and healthcare-associated APN. Neurogenic bladder, obstructive uropathy, urinary tract stone, bacteremia, and severe APN were more related to E. coli in healthcare-associated APN. In multivariate analysis, urinary catheter was more associated with K. pneumoniae (odds ratio [OR] 9.643, 95% confidence intervals [CI] 4.919-18.904, P = 0.001) and neurogenic bladder was more associated with E. coli (OR 3.765, 95% CI 1.112-12.772, P = 0.033). Extended-spectrum β-lactamase (ESBL) production was observed in 29.0% of E. coli in community-onset APN. Among ESBL, antimicrobial susceptibility of piperacillin/tazobactam was significantly higher in E. coli and ciprofloxacin was significantly higher in K. pneumoniae. CONCLUSION: K. pneumoniae were more associated with urinary catheter while E. coli tended to be more associated with urogenital problems. ESBL positivity showed no significance in healthcare-associated APN. In community-onset APN, ESBL producing E. coli was more observed than K. pneumoniae.